The traces of the last Pleistocene glacial maximum in the eastern Kamnik-Savinja Alps - Stojilković, Borut (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2017)
The area of the eastern Kamnik-Savinja Alps was glaciated in the time of the Last Pleistocene Glacial Maximum (LGM). The glacial landforms mentioned by the previous researchers and other landforms in the area were examined, gemorphologically mapped, morphographically and morphometrically analysed and a new map of the extent of the LGM was produced. The research revealed several glaciers in the area and that their sizes differed, primarily depending on the slope inclination direction.
Keywords: geomorfologija; geomorphology; Kamnik–Savinja Alps; Kamniško-Savinjske Alpe; ledena doba; pleistocen; Slovenia; Slovenija